Screening of Cry-Type Genes among Bacillus Thuringiensis Isolated from Soil Samples in Phereche and Sagarmatha National Park of Mount Everest Base Camp Region by PCR - Sahukhal, Gyan Sundar; Jayana, Bina Laxmi; Shrestha, Upendra Thapa; Dov, Eitan Ben; Agrawal, Viswa Nath Prasad (Journal of Food Science and Technology Nepal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The PCR method was performed to rapidly identify and classify Bacillus thuringiensis strains containing cry (crystal protein) genes toxic to species of Lepidoptera, Coleoptera, and Diptera using seven sets of universal primers namely Un-1, Un-2, Un-3, Un-4, Un-5, Un-7/8 and Un-9. Two sets of primers Un-cyt1 and Un-cyt-2 were also used to detect cytolytic genes. The technique enriches current strategies and simplifies the initial stages of large-scale screening of cry genes by pinpointing isolates that contain specific genes or unique combinations of interest with potential insecticidal activities, thus facilitating subsequent toxicity assays. Sixteen B. thuringiensis isolates were studied and the occurrences of cry1-type genes were found highest (68.75%) among the isolates, followed by cry7/8 and cry2 (56.25% and 50% respectively), cry4 and cry-9 (12.50% each) and finally cry5 among 6.25% isolates. Cry3 type genes were not detected among any isolates. Cyt2 types genes were detected among 12.50% isolates but cyt1 type genes were not detected in any of the isolates. Key words: Bacillus Thuringiensis; PCR, Soil; Everest Region Journal of Food Science and Technology Nepal Vol. 4, September, 2008, Page: 74-77